'What the Boers Did Australia Can Do, and Do Ten Times Better': The Impact of the Boers on Australian Defence Policy. Issue 3 (4th May 2022) - Lee, Alexander
Abstract: The Boer Republics of the South African Republic (Transvaal) and Orange Free State influenced Australian defence policy before the First World War. Despite the demise of the Boer Republics at the hands of the British Empire, and the participation of Australia in their defeat, Australian parliamentarians explicitly advocated replicating Boer-style concept of citizen-soldiers to counter an attack on the Commonwealth. The Second Anglo-Boer War (1899–1902) has received limited scholarly attention in Australia and the legislative legacy left by the Boers on early Australian defence policy has been near-entirely unmentioned. Impacted by the romanticised image of Boer society that permeated globally in the nineteenth Century and Australia's experiences fighting in the Second Anglo-Boer War, Australian legislators used the Boers as inspiration for constructing defence policy. Deeply impressed by the manner in which the Boer Republics resisted British annexation, particularly in the context of Australian fears regarding Japanese expansionism, there was a sustained attempt to legislate a Boer-style military system in Australia.